Resistance of eggplant (Solanum melongena L.) cultivars to Tetranychus ludeni Zacher (Acari:Tetranychidae) - Sierra-Monroy, Janeth Alexandra; Burbano-Figueroa, Oscar; Grandett-Martínez, Liliana María; Rodriguez-Pinto, Maria del Valle; Tordecilla-Zumaqué, Lilibet; Rubiano-Rodríguez, José Antonio (Agronomía Mesoamericana, 2021)
Introduction. Eggplant (Solanum melongena L. (Solanales: Solanaceae), one of the major vegetable crops in the Colombian Caribbean, is attacked by spider mites (Tetranychus ludeni (Acari: Tetranychidae) causing notable reductions in yield. Besides the substancial economic losses related to yield reduction, its control provokes environmental contamination due to excessive use of acaricide affecting the health of farmers and their families. Objective. The purpose of this study is to assess the resistance of seven eggplant cultivars to T. ludeni on field and greenhouse assays. Materials and methods. Eggplant landraces (Buelvas and Gonzalez), cultivars (C029 and C015), and breeding lines (C036, C025, C049) were assessed for resistance to T. ludeni. Field and greenhouse resistance assays were conducted in a randomized complete block design on field and greenhouse conditions (four replications for each accession). Results. Field assays showed significant differences in mite population density between eggplant cultivars (F=4.42; p<0.0004). C025 presented the highest mite population density while Buelvas had the lowest density. In the greenhouse assays, Buelvas showed lower mite density in comparison with the density observed in cultivar C036. Conclusions. Buelvas and Gonzalez exhibited resistance against T. ludeni providing evidence of the occurrence of field resistance in eggplant landraces from the Colombian Caribbean. The greenhouse assays, performed at high levels of mite density, offered greater discriminatory power and they are suitable for inclusion in the early phase of germplasm screening. We recommend the inclusion of cv. Buelvas as resistant reference genotype, and C036 as susceptible reference genotype in future screening trials. Cultivar Buelvas is recommended as reference genotype due to its reliable resistance level in field and greenhouse assays and its high yield.